Nurse led, primary care based antiretroviral treatment versus hospital care: a controlled prospective study in Swaziland - Bailey Kerry A; Mamvura Canaan T; Walley John; Wright John; Humphreys Ciaran P; Ntshalintshali Sweetness N; West Robert M; Philip Aby (BMC, 2010)
Abstract Background Antiretroviral treatment services delivered in hospital settings in Africa increasingly lack capacity to meet demand and are difficult to access by patients. We evaluate the effectiveness of nurse led primary care based antiretroviral treatment by comparison with usual hospital care in a typical rural sub Saharan African setting. Methods We undertook a prospective, controlled evaluation of planned service change in Lubombo, Swaziland. Clinically stable adults with a CD4 count > 100 and on antiretroviral treatment for at least four weeks at the district hospital were assigned to either nurse led primary care based antiretroviral treatment care or usual hospital care. Assignment depended on the location of the nearest primary care clinic. The main outcome measures were clinic attendance and patient experience. Results Those receiving primary care based treatment were less likely to miss an appointment compared with those continuing to receive hospital care (RR 0·37, p < 0·0001). Average travel cost was half that of those receiving hospital care (p = 0·001). Those receiving primary care based, nurse led care were more likely to be satisfied in the ability of staff to manage their condition (RR 1·23, p = 0·003). There was no significant difference in loss to follow-up or other health related outcomes in modified intention to treat analysis. Multilevel, multivariable regression identified little inter-cluster variation. Conclusions Clinic attendance and patient experience are better with nurse led primary care based antiretroviral treatment care than with hospital care; health related outcomes appear equally good. This evidence supports efforts of the WHO to scale-up universal access to antiretroviral treatment in sub Saharan Africa.